2004
DOI: 10.1128/jb.186.22.7490-7498.2004
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Inhibits Bap-Dependent Multicellular Behavior in Staphylococcus aureus

Abstract: Bap (biofilm-associated protein) is a 254-kDa staphylococcal surface protein implicated in formation of biofilms by staphylococci isolated from chronic mastitis infections. The presence of potential EF-hand motifs in the amino acid sequence of Bap prompted us to investigate the effect of calcium on the multicellular behavior of Bap-expressing staphylococci. We found that addition of millimolar amounts of calcium to the growth media inhibited intercellular adhesion of and biofilm formation by Bap-positive strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 52 publications
2
74
1
7
Order By: Relevance
“…Our results also demonstrated that the Ca 2ϩ inhibition of the Bap-mediated bacterial multicellular behavior was not due to repression of Bap expression. Instead, our results were consistent with the hypothesis that calcium causes a conformational change in Bap that affects its ability to form biofilms (1). The fact that calcium inhibition of Bapdependent biofilm formation takes place in vitro at concentrations similar to those found in milk serum supports the possibility that this inhibition could be important to the pathogenesis of the bacteria.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results also demonstrated that the Ca 2ϩ inhibition of the Bap-mediated bacterial multicellular behavior was not due to repression of Bap expression. Instead, our results were consistent with the hypothesis that calcium causes a conformational change in Bap that affects its ability to form biofilms (1). The fact that calcium inhibition of Bapdependent biofilm formation takes place in vitro at concentrations similar to those found in milk serum supports the possibility that this inhibition could be important to the pathogenesis of the bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, in addition to the genetic control here reported, we found that addition of millimolar amounts of calcium to the growth media inhibited intercellular adhesion and biofilm formation by Bappositive strain V329 (1). Our results also demonstrated that the Ca 2ϩ inhibition of the Bap-mediated bacterial multicellular behavior was not due to repression of Bap expression.…”
Section: Discussionsupporting
confidence: 75%
“…Calcium has been related to a variety of biological processes in bacteria (4,7,10), but its role in biofilm development is somewhat controversial. Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1). However, recent reports indicate that calcium promotes biofilm formation in other microorganisms, such as Xyllela fastidiosa or Vibrio vulnificus (4,7).…”
mentioning
confidence: 96%
“…A significant number of large proteins involved in cell surface and cell-cell interactions contain putative calcium binding domains (1,11,28). Calcium has been related to a variety of biological processes in bacteria (4,7,10), but its role in biofilm development is somewhat controversial.…”
mentioning
confidence: 99%
“…The fragment was then cloned into the BamHI site of the shuttle plasmid pMAD (1), and the resulting plasmid was transformed into the ⌬ B strain by electroporation, using a previously described protocol (13). Allelic exchange in the absence of a selection marker was performed as previously described (2). Briefly, the pMAD plasmid harboring a wild-type copy of the B gene was integrated into the chromosome through homologous recombination at a nonpermissive temperature (43.5°C).…”
Section: Methodsmentioning
confidence: 99%